In silico analysis of Triphala-derived polyphenols as inhibitors of TIR–TIR homodimerization in the inflammatory pathway - Rajendran, Durgadevi; Easwaran, Nalini (Frontiers in Bioinformatics, 2025)
Downstream signaling of the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) pathway is mediated by the adaptor protein myeloid differentiation primary response gene 88 (MyD88). The TIR domain present in MyD88 plays a pivotal role in regulating the expression of pro-inflammatory cytokines. Although synthetic drugs, including M20 and TJ-M2010-5, have been studied to mitigate the overexpression of MyD88, their prolonged usage is known to cause adverse side effects, highlighting the need for a safer, risk-free alternative. An Ayurvedic formulation named Triphala, which is rich in polyphenols and traditionally used to treat various ailments, was selected for this investigation. Although polyphenols are gaining attention as anti-inflammatory agents, their precise mode of action remains insufficiently understood. Previous studies have explored the anti-inflammatory properties of Triphala in a broad spectrum, but this study notably focuses on the interactions of Triphala-derived polyphenols with the TIR domain of the MyD88 adaptor protein in the NF-κB signaling pathway. This study employs computational docking and a molecular dynamics (MD) simulation to study the interaction and stability of the polyphenols with the target protein. The polyphenols were virtually docked to the TIR domain of MyD88 using AutoDock tools 1.5.7. Among them, the top three protein–polyphenol complexes with the highest binding affinities were selected and subjected to MD simulation for 200 ns to evaluate their interaction properties in detail. The findings of the MD simulation corroborated the docking results, showing that two complexes (protein–punicalagin and protein–chebulagic acid) demonstrated better interaction patterns. The MD trajectory revealed that polyphenol binding enhanced the stability of the target protein, as indicated by lower root-mean-square deviation (RMSD) (∼0.25 nm), solvent accessible surface area (SASA) (∼96.848–100.666 nm2), and stabilized radius of gyration (Rg) (∼1.50–1.53 nm) values for punicalagin and chebulagic acid complexes compared to the reference complex. Our findings have supported the hypothesis that Triphala polyphenols may interact with the TIR domain of MyD88, thereby inhibiting the production of inflammatory cytokines. This study provides a combination of computational validation of specific molecular targets and mechanistic insights into the anti-inflammatory potential of Triphala-derived polyphenols.